2021
DOI: 10.1515/ract-2020-0108
|View full text |Cite
|
Sign up to set email alerts
|

Efficient trace-scale extraction method of reactor produced 199Au adequate for nuclear medicine applications

Abstract: Production of no carrier-added (NCA) 199Au through natPt(n, γ) reaction and subsequent purification using liquid-liquid extraction from other radioisotopes is studied in the context of theranostic application. Comparative separation of NCA 199Au after dissolution of activated Pt target using three Cyanex compounds (Cyanex-272, Cyanex-302 and Cyanex-923) is evaluated. The extraction process is optimized in terms of the type of extractant, the concentration of extractant, extraction time and aqueous media (HNO3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Present study Present study 1 Trioctylphosphine oxide; 2 trialkylbenzylammonium chloride; 3 di-(2-ethylhexyl) phosphoric acid; 4 2-ethylhexyl phosphonic acid mono-2-ethylhexyl ester; 5 neodecanoic acid.…”
Section: Effect Of Metal Concentrationmentioning
confidence: 90%
See 3 more Smart Citations
“…Present study Present study 1 Trioctylphosphine oxide; 2 trialkylbenzylammonium chloride; 3 di-(2-ethylhexyl) phosphoric acid; 4 2-ethylhexyl phosphonic acid mono-2-ethylhexyl ester; 5 neodecanoic acid.…”
Section: Effect Of Metal Concentrationmentioning
confidence: 90%
“…The quality control examination, including radiometric and chemical purities, was carried out as described in [1,2] for the final purified 47 Sc product. The results demonstrated that the produced purified fraction of 47 Sc was free from 47 Ca, with the exception of contributions from 46 Sc and 48 Sc radionuclides, which could only be avoided or reduced to acceptable ratios by irradiating an enriched 46 Ca target.…”
Section: Quality Control Testsmentioning
confidence: 99%
See 2 more Smart Citations